PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MULTIMEDIA CERGAM TERHADAP KEMAMPUAN BERPIKIR KRITIS MATERI HAK DAN KEWAJIBAN KELAS III SEKOLAH DASAR - Siti Istithoah; Yulina Ismiyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by multimedia comics (CERGAM) on third-grade students' critical thinking skills in learning rights and obligations material. The research was conducted at SD Daarul Qur’an using a quantitative approach with a Pre-Experimental Design, specifically the One Group Pretest-Posttest Design. The research sample consisted of 19 third-grade students selected using saturated sampling technique. The instrument used was a descriptive test measuring critical thinking skills based on the revised Bloom’s Taxonomy indicators (C4, C5, and C6). Data were analyzed using a paired sample t-test. The results showed that the Sig. (2-tailed) value was 0.000 < 0.05, indicating a significant difference between pretest and posttest scores. These findings demonstrate that the implementation of the Problem Based Learning model assisted by multimedia CERGAM significantly improves students’ critical thinking skills. Therefore, integrating PBL with interactive visual media can create meaningful learning experiences and foster higher-order thinking skills in elementary school students.